Feeding more people on an increasingly fragile planet: China’s food and nutrition security in a national and global context - Fan, Shenggen; Brzeska, Joanna (Elsevier, 2014)
Developing and developed countries alike are increasingly facing the difficult question of how to feed more people amidst a host of emerging demographic, environmental, and health challenges. At the same time, in addition to food quantity, increased attention is being given to food quality attributes, in particular nutrition and safety. This is especially evident in China, where concerns are on the rise regarding the ability of China's food production systems to deliver nutritious and safe food to a growing, urbanizing and more affluent population. These food and nutrition concerns come at a time when China is an increasingly influential actor within the global food security network through activities such as production, consumption and trade. We argue that China has the opportunity to increase food and nutrition security both nationally and globally through a comprehensive policy agenda that focuses on institutional reforms, investments for and in agriculture, productive social safety nets, mutually beneficial trade, and the exchange of know-how and technologies among developing countries and donors. This agenda will help China adapt its food production systems to the changing face of agriculture and to play a vital role in addressing the emerging challenges facing food and nutrition security within and beyond China in the coming decades.